2021
DOI: 10.5187/jast.2021.e110
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of sodium long chain polyphosphate as a potential growth promoter in broilers

Abstract: Feasibility of sodium long chain polyphosphate as a potential growth promoter in broilers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…A polyphosphate derivative was found to have higher antibacterial activity against Gram-positive bacteria than against Gram-negative bacteria [15]. There is a possibility that Poly-p can isolate metal ions to stabilize, thus reducing the availability of nutrients to cells and making cells gradually become apoptotic [16,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A polyphosphate derivative was found to have higher antibacterial activity against Gram-positive bacteria than against Gram-negative bacteria [15]. There is a possibility that Poly-p can isolate metal ions to stabilize, thus reducing the availability of nutrients to cells and making cells gradually become apoptotic [16,6].…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental results have demonstrated several benefits of Poly-p for broilers. Moon et al [15] found that long chain Poly-p enhance the immune status based on broiler growth, which includes improved growth performance, organ development, blood and intestinal microflora constitution.…”
Section: Introductionmentioning
confidence: 99%
“…This experiment was designed with reference to our previous study [ 6 ]. A total of four hundred eighty 1-day-old male Ross 308 broilers were allocated to three treatment groups as follows: negative control group fed basal diet without additive (NC), positive control group fed basal diet containing 1 ppm of enramycin (PC), and the experimental group fed basal diet containing 0.1% ( v / w ) of P. konkukensis bacterial culture (PK), with 4 replicates (pens) per group of 40 birds each according to a completely randomly design.…”
Section: Methodsmentioning
confidence: 99%
“…The use of IFA has played a crucial role in increasing the economic effectiveness of the animal industry [ 3 ]. However, the use of IFA in inappropriate dosages and during prolonged periods may increase the emergence of drug-resistant strains of pathogens [ 4 , 5 , 6 ]. Furthermore, the imbalance of intestinal microbial composition through destruction of beneficial bacteria by IFA inclusion has led to the frequent incidence of gastrointestinal diseases with sub-optimal animal performance and may have subsequently increased the consumption of therapeutic antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Each treatment group had six replicates, where each replicate group housed 15 chicks with similar initial body weights. The provision of basal rations was divided into two phases, pre-feeding and post-feeding, while the composition and A c c e p t e d A r t i c l e calculated chemical composition of corn and soybean meal-based basal rations were formulated according to the 2017 Korean Poultry Feeding Standards and are listed in Table 1 [15].…”
Section: Experimental Design and Husbandrymentioning
confidence: 99%